The Role of Fiscal Policy in Human Development (Macroeconomic Approaches) - Ibrahim Hikmat Abbas; Seyedkamal Sadeghi (Newinera Publisher, 2022)
This study aims to analyze the relationship between financial policy and human development is one of the most prominent concerns of the modern era, as it is a way to know the impact and role of financial policy in the human development process, The main purpose of the research is to know The role of fiscal policy in human development the current study is looking for the future of human development in light of the developments that occurred in Iraq after 2003, Analysis of the reality of fiscal policy in Iraq.